Pengaruh Semangat Berorganisasi terhadap Prestasi Akademik Mahasiswa - Padli, Ruslan; Akbar, Ali (Sekolah Tinggi Agam Islam Sumatera Medan, 2023)
There are many things that affect student academic achievement, one of which is the activity of participating in organizational activities. But not a few also because of that students become complacent so that they take a long time to finish their studies. This study aims to determine the effect of organizational enthusiasm on academic achievement and how big the percentage of organizational enthusiasm is on student academic achievement. The method used in this study is a quantitative method with a series of tests, such as validity, reliability, normality, linear test, and simple linear test to test the validity of the variables and indicators in this study. As for the population in this study, there were 623 active students majoring in Islamic Communication and Broadcasting, Faculty of Da'wah and Communication, North Sumatra State Islamic University, Medan. The sample used in this study was 86 people obtained from the results of sampling using the slovin formula with a 10% allowance. Data collection techniques were carried out by distributing research questionnaires via the Google form. The results of the study answered that there was a significant influence between the organizational spirit variable and the academic achievement variable with an effect of 46.8%.